Aqueous battery film-forming additive and application thereof

By using the aqueous battery film forming additive in the aqueous battery, the insoluble fluoride solid electrolyte layer is generated through the replacement reaction, and the problems of high production cost of active materials when the solid electrolyte layer is introduced in the prior art are solved, and the battery performance and cycle life are improved.

CN119890486APending Publication Date: 2025-04-25YANGTZE RIVER DELTA PHYSICS RES CENT CO LTD +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202410462590.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-04-17
Publication Date
2025-04-25

Smart Images

  • Figure CN119890486A_ABST
    Figure CN119890486A_ABST
Patent Text Reader

Abstract

The embodiment of the invention relates to an aqueous battery film-forming additive and application thereof. The aqueous battery film-forming additive comprises: a fluoride AF soluble in an aqueous solution, an organic solution or an ionic liquid; in the fluoride AF, F is fluorine ion F <->, A is non-hydrated metal cations and comprises one or more metal cations of K < + >, Rb < + >, Cs < + >, Tl < + >, Sn < + >, Ag < + > and Sb < 3 + >, and an amino group; the aqueous battery film-forming additive is used in an electrode of an aqueous battery. The electrolyte of the aqueous battery comprises: a stable solution formed by dissolving a metal salt MX in an aqueous solution; in the aqueous battery, the fluoride AF and cations in the metal salt MX are subjected to a replacement reaction, and a solid electrolyte layer of the indissolvable fluoride MFx is generated on the surface of the negative electrode of the aqueous battery; wherein X is greater than 0.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of new energy storage devices, and in particular to an aqueous battery film-forming additive and application thereof. Background Art

[0002] Aqueous lithium-ion batteries have attracted much attention due to their absolute safety, low cost and environmental friendliness. However, due to the relatively narrow electrochemical window of aqueous solutions (only 1.23V), traditional electrode materials, especially negative electrode materials, cannot function in aqueous solutions. With the emergence of high-salt electrolytes (Science. 2015, 350, 6263), a solid electrolyte layer was first discovered at the negative electrode interface, expanding the electrochemical window of aqueous solutions to more than 3V. This breakthrough has greatly improved the energy density and cycle performance of aqueous batteries.

[0003] Currently, there are two main methods for applying solid electrolyte layers in batteries: one is to use aqueous electrolytes with high salt concentrations, and the other is to use pre-prepared solid electrolyte films. Each of these two methods has its own advantages and disadvantages.

[0004] The solid electrolyte layer is gradually formed during the battery cycle by using a high-salt concentration aqueous electrolyte: by increasing the salt concentration in the aqueous electrolyte, the formation of the solid electrolyte layer can be promoted, thereby broadening the electrochemical window of the battery. However, this method requires a high-concentration salt solution, which may increase the viscosity of the electrolyte and affect the ion conductivity of the battery. In addition, in the process of forming the solid electrolyte layer, it will still compete with the hydrogen evolution reaction, resulting in irreversible loss of active lithium in the positive electrode.

[0005] By directly introducing the pre-prepared solid electrolyte film into the battery, the solid electrolyte film can be obtained in advance through a specific preparation method, and the quality and structure are easier to control, which can improve the consistency and stability of the battery. However, the preparation of solid electrolyte films requires additional steps and costs, which increases the complexity and cost of battery preparation; the preparation process may require high temperature or special conditions, which is not conducive to large-scale industrial production. In addition, the solid electrolyte film introduced by this method may have defects at the interface in contact with the electrode material, affecting the performance and cycle life of the battery.

[0006] In summary, the existing methods of introducing solid electrolyte layers into batteries all have certain technical defects, such as active material loss, high energy consumption, and high production costs, which need to be solved through further technological improvements. Summary of the invention

[0007] The purpose of the present invention is to provide an aqueous battery film-forming additive and its application in view of the defects of the prior art, which is a fluoride AF soluble in aqueous solution, organic solution or ionic liquid. The fluoride AF reacts with the cation M in the electrolyte to generate an insoluble compound MF through a replacement reaction. x Solid electrolyte layer, the whole process is fast and does not consume the active lithium in the electrode material, thereby improving the cycle performance of the battery. The non-hydrated metal cation A in the aqueous battery film-forming additive is used to induce the anions in the electrolyte to enter the double-layer structure of the negative electrode interface under the interaction of anions and cations. During the cycle of the aqueous battery, when the potential of the negative electrode reaches a certain threshold, the F-containing group in the anion can continue to accept electrons to generate F - ;Thus, the insoluble fluoride MF is further generated on the negative electrode surface under the induction and electrochemical action of the non-hydrated metal cation A. x Solid electrolyte layer. To achieve the above object, the present invention provides an aqueous battery film-forming additive, comprising: a fluoride AF soluble in an aqueous solution, an organic solution or an ionic liquid;

[0008] In the fluoride AF, F is a fluoride ion F - , A is a non-hydrated metal cation, including K + , Rb + , Cs + , T l + Sn 2 + 、Ag + , Sb 3+ One or more metal cations, and an amino group, when A is an amino group, the fluoride AF is a quaternary ammonium fluoride;

[0009] The aqueous battery film-forming additive is used in the electrode of the aqueous battery; the electrolyte of the aqueous battery includes: a stable solution formed by dissolving a metal salt MX in an aqueous solution; in the aqueous battery, the fluoride AF undergoes a replacement reaction with the cations in the metal salt MX to generate a sparingly soluble fluoride MF on the negative electrode surface of the aqueous battery x solid electrolyte layer; wherein, X>0.

[0010] Preferably, in the metal salt MX, M is a cation, including alkaline metal ions, alkaline earth metal ions, Zn 2+ or Al 3+ One or more of; X is an anion, including, CF3SO3 - 、TFS I - , FS I - , BET I - ,OTf - 、BF4 - PF6- 、AsF6 - 、CF3C00 - One or more of the .

[0011] Preferably, the concentration of the electrolyte is 0.001 mol / kg-100 mol / kg; or, the concentration of the electrolyte is 0.001 mol / L-100 mol / L.

[0012] Preferably, the solubility of the fluoride AF in an aqueous solution, an organic solution or an ionic liquid is: within a temperature range of 0°C to 100°C, the mass of the fluoride AF dissolved in every 100g of solvent is 0.01-1000g.

[0013] Preferably, the non-hydrated metal cation A in the aqueous battery film-forming additive is used to modulate the double-layer structure of the negative electrode interface, thereby reducing the decomposition side reaction of the solvent molecules in the electrolyte at the negative electrode interface.

[0014] Preferably, the non-hydrated metal cation A in the aqueous battery film-forming additive is used to induce the anions in the electrolyte to enter the double electric layer structure of the negative electrode interface under the interaction between anions and cations;

[0015] Wherein, when the anion is CF3SO3 - 、TFS I - , FS I - , BET I - ,OTf - 、BF4 - PF6 - 、AsF6 - 、CF3C00 - , when the potential of the negative electrode reaches a certain threshold during the cycle of the aqueous battery, the F-containing group in the anion can continue to accept electrons to generate F - ; Thus, through the induction and electrochemical action of the non-hydrated metal cation A, the insoluble fluoride MF is further generated on the surface of the negative electrode x Solid electrolyte layer.

[0016] In a second aspect, an embodiment of the present invention provides an application method of an aqueous battery film-forming additive, the method comprising: adding the aqueous battery film-forming additive described in the first aspect to an electrode active material dissolved in an aqueous solution, an organic solution or an ionic liquid, stirring, and then volatilizing the solvent to obtain an electrode material to which the aqueous battery film-forming additive is added;

[0017] Among them, the mass of the aqueous battery film-forming additive accounts for 0.0001%-50.0000% of the total mass of the electrode material added with the aqueous battery film-forming additive; the stirring time is 1-100h; and the volatilization temperature is -100℃-1000℃.

[0018] In a third aspect, an embodiment of the present invention provides an application method of an aqueous battery film-forming additive, the method comprising: mixing an electrode active material, the aqueous battery film-forming additive described in the first aspect, a conductive agent, and a binder to prepare an electrode slurry, and coating the electrode slurry on a current collector to obtain an electrode sheet;

[0019] The mass of the aqueous battery film-forming additive accounts for 0.0001%-50.0000% of the total mass of the electrode material.

[0020] In a fourth aspect, an embodiment of the present invention provides an electrode for an aqueous battery, comprising the aqueous battery film-forming additive described in the first aspect.

[0021] In a fifth aspect, an embodiment of the present invention provides an aqueous battery, comprising the electrode of the aqueous battery described in the fourth aspect.

[0022] Preferably, the positive electrode active material of the aqueous battery includes: LiMn2O4, LiFePO4, LiCoO2, Lini x Co y Mn 1-x-y O2、L i N i x Co y A l 1-x-y Any of O2; wherein x>0, y>0, x+y<1;

[0023] The negative electrode active material of the aqueous battery includes anatase TiO2, TiO2(B), Mo6S8, Li4T i5O 12 , Li Ti2(P04)3, graphite, or silicon.

[0024] Preferably, the aqueous battery specifically includes: any one of an aqueous lithium battery, an aqueous sodium battery, an aqueous potassium battery, an aqueous zinc battery, an aqueous magnesium battery, an aqueous calcium battery, and an aqueous aluminum battery.

[0025] Preferably, the aqueous battery is used in energy storage power stations, mobile power sources for portable devices, and power devices for electric vehicles or hybrid electric vehicles.

[0026] The aqueous battery film-forming additive provided in the embodiment of the present invention is a fluoride AF that is soluble in an aqueous solution, an organic solution or an ionic liquid. The aqueous battery film-forming additive is added to the electrode material. After the aqueous battery is assembled, it reacts with the metal cations in the electrolyte through a replacement reaction to form a sparingly soluble fluoride solid electrolyte layer, forming a good ion conductor and electronic insulator on the electrode surface, which can prevent the solvent molecules in the electrolyte from decomposing or the electrode material from deforming. The whole process is fast and does not consume the active lithium in the electrode material, which can effectively improve the performance of the battery; at the same time, during the charging process of the aqueous battery, the non-hydrated cation A in the aqueous battery film-forming additive will continue to accumulate at the interface where the negative electrode and the electrolyte are in contact under the action of the electric field, thereby preventing the solvent molecules in the electrolyte from reacting with hydrogen at the negative electrode interface to the greatest extent; in addition, the non-hydrated cation A brings the anions in the electrolyte into the negative electrode interface double layer through the interaction between anions and cations, which can promote the formation of the negative electrode solid electrolyte layer. BRIEF DESCRIPTION OF THE DRAWINGS

[0027] Figure 1 A schematic diagram of the principle of the aqueous battery film-forming additive provided by an embodiment of the present invention to construct a stable interface environment at the negative electrode interface;

[0028] Figure 2 is the non-hydrated cation Cs in the embodiment of the present invention + Schematic diagram of modulating the double-layer structure of the negative electrode interface;

[0029] Figure 3 This is a schematic diagram of the synthesis of the aqueous battery film-forming additive CsF used in the negative electrode to form the negative electrode material TiO2-5wt%CsF in the embodiment of the present invention;

[0030] Figure 4 The characterization curve of X-ray photoelectron spectroscopy (XPS) for the negative electrode sheet in the embodiment of the present invention;

[0031] Figure 5 This is an XPS graph of the Cs signal of the battery electrode before and after the in-situ formation of the SE I film by dropping the electrolyte in the embodiment of the present invention;

[0032] Figure 6 This is an XPS image of a battery electrode after in-situ generation of an SE I film in an embodiment of the present invention;

[0033] Figure 7 This is a high-resolution transmission electron microscope (TEM) image of an in-situ generated SE I film in an embodiment of the present invention;

[0034] Figure 8 Schematic diagram of generating SE I containing LiF by reacting the film-forming additive CsF with the electrolyte in an embodiment of the present invention;

[0035] Fig. 9 The curves of in-situ electrochemical differential mass spectrometry (DEMS) test of two full batteries in Example 1 of the present invention;

[0036] Fig.10 1 is a comparison curve of the cycle performance of two full batteries in Example 1 of the present invention;

[0037] Fig.11 The coulombic efficiency comparison of two full batteries in Example 1 of the present invention is shown in FIG.

[0038] Fig.12 This is a schematic diagram of the long cycle performance of the battery at 10C rate in Example 1 of the present invention;

[0039] Fig.13 This is a charge and discharge curve diagram of the first week of the mAh-level soft-pack battery in Example 1 of the present invention;

[0040] Fig.14 This is a cycle performance diagram of the mAh-level soft-pack battery in Example 1 of the present invention;

[0041] Fig.15 The first week charge and discharge curve of the Ah-class soft-pack battery in Example 1 of the present invention;

[0042] Fig.16 This is a cycle performance diagram of a TiO2 full battery with a film-forming additive CsF added in Example 1 of the present invention, which is enlarged into an Ah-level soft-pack battery;

[0043] Fig.17 This is a long cycle energy efficiency curve of the TiO2 full battery with the film-forming additive CsF added in Example 1 of the present invention, which is enlarged to the Ah level. DETAILED DESCRIPTION

[0044] In order to make the purpose, technical scheme and advantages of the present invention clearer, the present invention will be further described in detail below with reference to the accompanying drawings. Obviously, the described embodiments are only part of the embodiments of the present invention, rather than all the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0045] The technical solution of the present invention is further described in detail below through the accompanying drawings and embodiments.

[0046] The aqueous battery film-forming additive provided in the embodiment of the present invention is used in the positive electrode or negative electrode of the battery. By adding the aqueous battery film-forming additive to the electrode and then assembling the battery, a replacement reaction occurs with the metal cations in the electrolyte to generate a solid electrolyte layer on the surface of the battery electrode.

[0047] The aqueous battery film-forming additive of the present invention comprises: fluoride AF which is soluble in aqueous solution, organic solution or ionic liquid.

[0048] In fluoride AF, F is the fluoride ion F - , A is a non-hydrated metal cation, including K + , Rb + , Cs + , T l + Sn 2+ 、Ag + , Sb 3+ One or more metal cations, and amino groups.

[0049] When A is an amino group, the fluoride AF is a quaternary ammonium fluoride salt, preferably tetraethylammonium fluoride hydrate, tetrabutylammonium fluoride, tetrabutylammonium fluoride hydrate, tetramethylammonium fluoride tetrahydrate, tetraethylammonium fluoride trihydrofluoride, and the like.

[0050] The electrolyte in the aqueous battery using the aqueous battery film-forming additive of the present invention comprises: a stable solution formed by dissolving the metal salt MX in an aqueous solution. The concentration of the electrolyte is 0.001 mol / kg-100 mol / kg, or 0.001 mol / L-100 mol / L.

[0051] In the above metal salt MX, M is a cation, including alkaline metal ions, alkaline earth metal ions, Zn 2+ or A l 3+ One or more of; X is an anion, including CF3SO3 - 、TFS I - , FS I - , BET I - ,OTf - 、BF4 - PF6 - 、AsF6 - 、C lO4 - 、CF3C00 - One or more of the .

[0052] Through the assembled aqueous battery, the electrode containing the film-forming additive is in contact with and infiltrated with the electrolyte, so that the film-forming additive is dissolved in the aqueous battery electrolyte.

[0053] In the aqueous battery of the present invention, the fluoride AF undergoes a substitution reaction with the cation M in the metal salt MX to generate a sparingly soluble fluoride MF on the negative electrode surface of the aqueous battery. x Solid electrolyte layer; wherein X>0. The sparingly soluble fluoride MF generated xThe solid electrolyte layer forms a good ion conductor and electronic insulator on the electrode surface, which can prevent the solvent molecules in the electrolyte from decomposing or the electrode material from deforming. The whole process occurs quickly after the battery is assembled. In addition, the cations in the solid electrolyte layer come from the electrolyte rather than the positive electrode material, so they do not consume the activity in the electrode material. Therefore, the use of the above-mentioned aqueous battery film-forming additive can effectively improve the performance of the battery.

[0054] The negative electrode interface in aqueous batteries is a very important area, which directly affects the performance and cycle life of the battery. There are two phase interactions at the electrode / solution interface: one is the electrostatic effect caused by the residual charge in the two phases of the electrode and the solution; the other is the short-range interaction between the electrode and various particles in the solution (ions, solute molecules and solvent molecules, etc.), such as characteristic adsorption, dipole directional arrangement, etc. These two phase interactions determine the structure and properties of the interface. The area of ​​charge distribution at the interface constitutes a double electric layer structure.

[0055] The non-hydrated metal cations in the aqueous battery film-forming additive of the present invention also play a role in modulating the double-layer structure of the negative electrode interface, thereby reducing the decomposition side reaction of the solvent molecules in the electrolyte at the negative electrode interface.

[0056] In addition to the above-mentioned non-hydrated metal cations that can form a stable solid electrolyte film on the surface of the negative electrode together with the fluoride ions, forming a barrier effect, blocking solvent molecules and other unnecessary components in the electrolyte from entering the double-layer region of the negative electrode surface, making it more difficult for the solvent molecules to react with the negative electrode, the excess non-hydrated metal cations carry a positive charge and gather on the surface of the negative electrode to attract the anions in the electrolyte. This attraction will prompt these ions to form a relatively stable double-layer structure on the surface of the negative electrode, reducing their direct contact with the negative electrode material. Therefore, the presence of non-hydrated metal cations can enhance the interaction between the negative electrode surface and the electrolyte and improve the stability of the interface. This helps to reduce the possibility of side reactions on the negative electrode surface, while promoting the adsorption and migration of ions on the negative electrode surface, which is beneficial to the performance improvement and cycle life extension of aqueous batteries.

[0057] Furthermore, in aqueous batteries, normally, water molecules receive electrons at the negative electrode to undergo hydrolysis and are decomposed into hydrogen and hydroxyl ions. However, in the aqueous batteries of the present invention, the non-hydrated cations A in the aqueous battery film-forming additives will continue to accumulate at the interface where the negative electrode and the electrolyte are in contact under the action of the electric field during the charging process of the aqueous battery. Therefore, the accumulated cations can prevent the hydrogen evolution reaction of the solvent molecules in the electrolyte at the negative electrode interface to the greatest extent.

[0058] In addition, the non-hydrated cation A induces the anions in the electrolyte to enter the double-layer structure of the negative electrode interface through the interaction between anions and cations, bringing the anions in the electrolyte into the double-layer structure of the negative electrode interface, thereby promoting the formation of the negative electrode solid electrolyte layer. Especially when the anion has a F-containing group, such as CF3SO3 - 、TFS I - , FS I - , BET I - ,OTf - 、BF4 - PF6 - 、AsF6 - 、CF3C00 - When one or more of the above are present, during the cycle of the aqueous battery, when the potential of the negative electrode reaches a certain threshold (corresponding to different anions, around 2.30-2.90 V, all relative to Li + / L i), the F-containing group in the anion can continue to accept electrons to generate F - , which is equivalent to further anion reduction. Therefore, under the induction and electrochemical action of the non-hydrated metal cation A, the insoluble fluoride MF can be further generated on the negative electrode surface. x Solid electrolyte layer.

[0059] In summary, the aqueous battery film-forming additive provided by the embodiment of the present invention is a fluoride AF that is soluble in an aqueous solution, an organic solution or an ionic liquid. The aqueous battery film-forming additive is added to the electrode material and introduced into the battery system. After the aqueous battery is assembled, it reacts with the metal cations in the electrolyte through a replacement reaction to form a sparingly soluble fluoride solid electrolyte layer, forming a good ion conductor and electronic insulator on the electrode surface, which can prevent the solvent molecules in the electrolyte from decomposing or the electrode material from deforming. The whole process is fast and does not consume the active lithium in the electrode material, which can effectively improve the performance of the battery; at the same time, during the charging process of the aqueous battery, the non-hydrated cation A in the aqueous battery film-forming additive will continue to accumulate at the interface where the negative electrode and the electrolyte are in contact under the action of the electric field, thereby preventing the solvent molecules in the electrolyte from reacting with hydrogen at the negative electrode interface to the greatest extent; in addition, the non-hydrated cation A brings the anions in the electrolyte into the negative electrode interface double layer through the interaction between anions and cations, which can promote the formation of the negative electrode solid electrolyte layer.

[0060] The aqueous battery film-forming additive of the present invention is introduced into the battery system by the following methods. The following two methods are only the methods used in the implementation of the present invention, but the actual method of applying the film-forming additive to the electrode is not limited to these two methods.

[0061] The first method is to add the aqueous battery film-forming additive to the electrode active material dissolved in the aqueous solution, organic solution or ionic liquid, stir, and then evaporate the solvent to obtain the electrode material added with the aqueous battery film-forming additive. More specifically, the order of adding materials to the aqueous solution, organic solution or ionic liquid is preferably: electrode active material, aqueous battery film-forming additive, conductive agent and binder.

[0062] The solubility of fluoride AF in aqueous solution, organic solution or ionic liquid is as follows: within the temperature range of 0°C to 100°C, the mass of fluoride AF dissolved in every 100g of solvent is 0.01-1000g.

[0063] The mass of the aqueous battery film-forming additive accounts for 0.0001%-50.0000% of the total mass of the electrode material to which the aqueous battery film-forming additive is added; the stirring time is 1-100 hours; the volatilization temperature is -100°C-1000°C, and the specific temperature and time can be determined by the technical personnel in this field according to the actual needs of the aqueous solution, organic solution or ionic liquid selected. The solvent is volatilized during the electrode preparation process and will not enter the battery system.

[0064] The second method is to make electrode active materials, aqueous battery film-forming additives, conductive agents and binders into electrode slurry, and apply it on the current collector to obtain electrode plates; wherein the mass of the aqueous battery film-forming additive accounts for 0.0001%-50.0000% of the total mass of the electrode material to which the aqueous battery film-forming additive is added.

[0065] The aqueous battery film-forming additive of the present invention can be added to the positive electrode material or the negative electrode material without affecting its entry into the electrolyte after the battery is assembled.

[0066] When it is applied to positive electrode materials, the positive electrode active materials that can be used include but are not limited to: LiMn2O4, LiFePO4, LiCoO2, Lini x Co y Mn 1-x-y O2、L i N i x Co y A l 1-x-y Any one of O2; wherein x>0, y>0, x+y<1.

[0067] When it is applied to negative electrode materials, the negative electrode active materials that can be used include but are not limited to: anatase TiO2, TiO2(B), Mo6S8, Li4T i5O 12 , Li Ti2(P04)3, graphite, or silicon.

[0068] The aqueous battery of the present invention may specifically include: the aqueous battery specifically includes: any one of an aqueous lithium battery, an aqueous sodium battery, an aqueous potassium battery, an aqueous zinc battery, an aqueous magnesium battery, an aqueous calcium battery, and an aqueous aluminum battery; it can be applied to energy storage power stations, mobile power sources for portable devices, power devices for electric vehicles or hybrid electric vehicles, etc.

[0069] The above introduces the aqueous battery film-forming additive of the present invention and its application method and principle. The following uses several specific embodiments to illustrate its actual application method and performance.

[0070] Example 1

[0071] The present invention provides a film-forming additive for aqueous lithium-ion batteries, which is cesium fluoride (CsF). In the aqueous lithium-ion battery, the negative electrode active material is nano-sized TiO2, the positive electrode active material is spinel-phase LiMn2O4, the aqueous electrolyte is 13.8 mol / kg LiTFSI, and the solvent is water.

[0072] Figure 1 The aqueous battery film-forming additive provided in the embodiment of the present invention generates an ion conductor and an electronically insulating solid electrolyte layer (SE I) film in situ at the negative electrode interface, inducing anion reduction in a place without SE I (i.e., TFS I - The -CF3 obtained in the reaction continues to accept electrons to generate F - ), cations gather in the area without SE I membrane to achieve the schematic diagram of the regulation of the double electric layer at the negative electrode interface. Through the SE I generation, cation aggregation and induced reduction of anions as shown in the figure, a stable interface environment can be built for the negative electrode interface.

[0073] Figure 2 is the non-hydrated cation Cs in the embodiment of the present invention + Schematic diagram of the principle of modulating the double-layer structure of the negative electrode interface. Non-hydrated cation Cs + It can destroy the hydrogen bond network at the negative electrode interface and inhibit the hydrogen evolution side reaction at the negative electrode interface. At the same time, the non-hydrated cations can also bring anions to the double electric layer at the negative electrode interface through the interaction between anions and cations, further promoting the formation of the solid electrolyte layer.

[0074] In this embodiment 1, the method of using CsF film-forming additive is as follows: 500 mg TiO2 and 25 mg CsF are added to anhydrous ethanol solution, stirred at room temperature for 4 hours, and then dried at 100°C for 12 hours to obtain the final product TiO2-5 wt% CsF. The synthesis process is as follows: Figure 3 shown.

[0075] The synthesized negative electrode material, conductive additive and binder are prepared into electrode slurry in a mass ratio of 7:2:1, and then the slurry is coated on the aluminum foil current collector to prepare the negative electrode sheet. The prepared negative electrode sheet is characterized by X-ray photoelectron spectroscopy (XPS), such as Figure 4 From the XPS characterization, it can be identified that the peak at 688eV is the peak of the binder PVDF, and the peak at 685eV is the peak of CsF.

[0076] Figure 5 The XPS graph of the Cs signal of the battery electrode before and after the in-situ formation of SE I film by dropping electrolyte in the embodiment of the present invention is shown. It can be seen that before the in-situ formation of SE I film, the double peaks appear in pairs in XPS, the orbital energy level is split, and the relative intensity of the orbital split into d3 / 2:d5 / 2 is 2:3 respectively. Therefore, according to Figure 5 XPS signal about Cs ( Figure 5 The curve in the upper middle part of the figure shows the presence of CsF before the addition of the electrolyte. Since CsF has a high solubility in aqueous solution, the signal of Cs disappears after the addition of 13.8 mol / Kg Li TFS I, an aqueous electrolyte. Figure 5 lower middle curve).

[0077] Figure 6 The XPS graph of the battery pole piece after the in-situ generation of the SE I film in the embodiment of the present invention is shown. Figure 5 It was observed that the Cs signal disappeared after adding the electrolyte, which can be inferred Figure 6 The peak at 685 eV is the signal of LiF, which proves that CsF can undergo a replacement reaction in aqueous electrolyte to generate LiF.

[0078] The replacement reaction can be confirmed by high-resolution transmission electron microscopy (TEM), such as Figure 7 The lattice spacing of 0.2nm is the (200) plane of LiF, while the lattice spacing of 0.35nm is the (101) plane of TiO2 main phase. Therefore, the occurrence of substitution reaction is also proved according to the TEM image.

[0079] In this embodiment 1, the film-forming additive CsF reacts with the electrolyte to generate an SE containing LiF. Figure 8 shown.

[0080] In this Example 1, LiMn2O4 was used as the positive electrode, 13.8 mol / Kg LiTFSI was used as the aqueous electrolyte, and TiO2 with CsF as the film-forming additive and TiO2 without CsF as the negative electrode were assembled into two full cells for in-situ electrochemical differential mass spectrometry (DEMS) testing. The test results are shown in Figure 1. Fig. 9As shown in the figure, there are two obvious hydrogen evolution peaks in both full cells. The hydrogen evolution rates of the two hydrogen evolution peaks of the CsF-free TiO2 full cell are 19.9 nmol·min -1 mg -1 and 21.3 nmol·min -1 mg -1 The hydrogen evolution rates of the two hydrogen evolution peaks of the TiO2 full cell with the addition of the film-forming additive CsF are 14.3 nmol·min -1 mg -1 and 6.3 nmol·min -1 mg -1 The total amount of hydrogen evolution in the TiO2 full cell without CsF is 15907.4 nmol, and the total amount of hydrogen evolution in the TiO2 full cell with the addition of the film-forming additive CsF is 10351.6 nmol. It can be seen that the CsF film-forming additive can effectively inhibit the side reaction of hydrogen evolution in aqueous batteries.

[0081] In this embodiment 1, TiO2 with CsF as the film-forming additive and TiO2 without CsF were used as negative electrode materials, lithium manganate was used as the positive electrode material, 13.8 mol / Kg LiTFSI was used as the electrolyte, and aluminum foil was used as the current collector for the positive and negative electrodes to assemble the full battery. The test results are shown in Figure 1. Fig.10 As shown: the first week discharge capacity of the TiO2 full battery with the film-forming additive CsF at a rate of 0.74C is 142.769mAh / g (calculated based on the mass of the negative electrode), and the capacity retention rate after 300 cycles is 81%. The first week discharge capacity of the TiO2 full battery without CsF at a rate of 0.74C is 141.234mAh / g (calculated based on the mass of the negative electrode), and the capacity retention rate after 93 cycles is 42%. Comparing the coulombic efficiency of the two batteries, the coulombic efficiency of the TiO2 full battery with the film-forming additive CsF can reach 98.7%, while the coulombic efficiency of the TiO2 full battery without CsF is 96%, as shown in Figure 1. Fig.11 The full battery of TiO2 with the addition of the film-forming additive CsF has a discharge capacity of 102.226 mAh / g (calculated based on the mass of the negative electrode) in the first week at a rate of 10C, and a capacity retention rate of 76% after 2000 cycles. Fig.12 The specific test results are recorded in Table 1.

[0082] The TiO2 full battery with the addition of film-forming additive CsF is enlarged into a mAh-level soft-pack battery, such as Fig.13 As shown in the figure, the capacity of the soft pack battery is 14.769 mAh. At a rate of 0.74C, the capacity retention rate is 71% after 1000 cycles and 61% after 1558 cycles. Fig.14 The specific test results are recorded in Table 2.

[0083] The TiO2 full battery with the addition of the film-forming additive CsF is enlarged into an Ah-level soft-pack battery, such as Fig.15 As shown in Figure 1, the capacity of the soft pack battery is 1.056Ah and the energy density is 57Wh / kg. The capacity retention rate is 70% after 220 cycles at a rate of 1.5C. Fig.16 The energy efficiency of the battery is 87% at 1.5C. Fig.17 The specific test results are recorded in Table 3.

[0084] Example 2

[0085] This embodiment provides a film-forming additive for an aqueous lithium-ion battery, which is cesium fluoride (CsF). In the aqueous lithium-ion battery, the negative electrode active material is anatase phase TiO2, the positive electrode active material is lithium manganate, the aqueous electrolyte is 13.8 mol / kg LiTFSI, and the solvent is water.

[0086] In this embodiment 2, the CsF film-forming additive is used as follows: anatase phase titanium dioxide is mixed with a conductive additive, a CsF film-forming additive, and a binder in a mass ratio of 7:1.5:0.5:1 to form an electrode slurry, and then the slurry is coated on an aluminum foil current collector to form a negative electrode sheet.

[0087] The TiO2 pole piece with CsF added and the TiO2 pole piece without CsF added were used as the negative pole piece, lithium manganese oxide was used as the positive electrode material, 13.8 mol / Kg Li TFS I was used as the electrolyte, and aluminum foil was used as the current collector of the positive and negative electrodes to assemble the full battery. The first week discharge capacity of the full battery assembled with the TiO2 pole piece with CsF added was 141.934 mAh / g (calculated based on the mass of the negative electrode) at a rate of 0.5C, and the capacity retention rate after 500 cycles was 79%. The first week discharge capacity of the full battery assembled with the TiO2 pole piece without CsF added was 140.526 mAh / g (calculated based on the mass of the negative electrode) at a rate of 0.5C, and the capacity retention rate after 100 cycles was 39%. Comparing the coulombic efficiency of the two batteries, the coulombic efficiency of the whole battery assembled with the TiO2 pole piece with CsF added can reach 99.1%, while the coulombic efficiency of the whole battery assembled with the TiO2 pole piece without CsF added is 95.8%. The first week discharge capacity of the whole battery assembled with the TiO2 pole piece with CsF added is 101.326mAh / g (calculated based on the mass of the negative electrode) at a rate of 10C, and the capacity retention rate after 2000 cycles is 81%. The results are recorded in Table 1.

[0088] The full battery assembled with the TiO2 pole piece added with CsF was enlarged into a mAh-level soft-pack battery, the capacity of the soft-pack battery was 15.698 mAh, and the capacity retention rate was 60% after 1600 cycles at a rate of 0.5C. The results are recorded in Table 2.

[0089] The full battery assembled with CsF-added TiO2 pole pieces was enlarged into an Ah-level soft-pack battery, with a capacity of 1.156Ah and an energy density of 56Wh / kg. The capacity retention rate was 72% after 300 cycles at a rate of 1.5C. The energy efficiency of the battery was 89% at 1.5C. The results are recorded in Table 3.

[0090] Example 3

[0091] This embodiment provides a film-forming additive for aqueous lithium-ion batteries, which is tetrabutylammonium fluoride (C 16 H 36 NF, TBAF). In the aqueous lithium-ion battery, the negative electrode active material is anatase phase TiO2, the positive electrode active material is lithium manganate, the aqueous electrolyte is 13.8 mol / kg LiTFSI, and the solvent is water.

[0092] In this embodiment 2, the CsF film-forming additive is used as follows: 500 mg TiO2 and 25 mg TBAF are added to an anhydrous ethanol solution, stirred at room temperature for 4 hours, and then dried at 100°C for 12 hours to obtain the final product TiO2-5 wt% TBAF.

[0093] The TiO2 with the film-forming additive TBAF and the TiO2 without TBAF were used as negative electrode materials, lithium manganese oxide as positive electrode material, 13.8 mol / Kg LiTFSI as electrolyte, and aluminum foil as current collectors for positive and negative electrodes to assemble full batteries. The full battery of TiO2 treated with TBAF had a discharge capacity of 140.065 mAh / g (based on the mass of the negative electrode) in the first week at a rate of 0.5C, and a capacity retention rate of 77% after 400 cycles. The full battery of TiO2 without TBAF had a discharge capacity of 139.786 mAh / g (based on the mass of the negative electrode) in the first week at a rate of 0.5C, and a capacity retention rate of 31% after 100 cycles. Comparing the coulombic efficiency of the two batteries, the coulombic efficiency of the full battery of TiO2 with TBAF can reach 99.3%, while the coulombic efficiency of the full battery without TBAF is 96.2%. The full battery with TiO2 added with TBAF has a first-week discharge capacity of 100.289 mAh / g (calculated based on the mass of the negative electrode) at a rate of 10C, and a capacity retention rate of 82% after 2000 cycles. The results are recorded in Table 1.

[0094] The TiO2 full battery with TBAF added was enlarged into a mAh-level soft-pack battery, the capacity of which was 16.796 mAh, and the capacity retention rate was 65% after 1800 cycles at a rate of 0.5C. The results are recorded in Table 2.

[0095] The TiO2 full battery with TBAF added was enlarged into an Ah-level soft-pack battery. The capacity of the soft-pack battery was 1.432Ah and the energy density was 58Wh / kg. The capacity retention rate was 79% after 500 cycles at a rate of 1.5C. The energy efficiency of the battery was 92% at 1.5C. The results are recorded in Table 3.

[0096] Example 4

[0097] This embodiment provides a film-forming additive for aqueous lithium-ion batteries, which is tetrabutylammonium fluoride (C 16 H 36 NF, TBAF). In the aqueous lithium-ion battery, the negative electrode active material is anatase phase TiO2, the positive electrode active material is lithium manganate, the aqueous electrolyte is 13.8 mol / kg LiTFSI, and the solvent is water.

[0098] In this embodiment, the TBAF film-forming additive is used as follows: anatase phase titanium dioxide, a conductive additive, a TBAF film-forming additive, and a binder are prepared into an electrode slurry in a mass ratio of 7:1.5:0.5:1, and the slurry is then coated on an aluminum foil current collector to form a negative electrode sheet.

[0099] The TiO2 pole piece with TBAF added and the TiO2 pole piece without TBAF added were used as the negative electrode, lithium manganese oxide was used as the positive electrode material, 13.8 mol / Kg LiTFSI was used as the electrolyte, and aluminum foil was used as the current collector of the positive and negative electrodes to assemble the full battery. The first week discharge capacity of the full battery assembled with the TiO2 pole piece with TBAF added was 146.768 mAh / g (calculated based on the mass of the negative electrode) at a rate of 0.5C, and the capacity retention rate after 500 cycles was 79%. The first week discharge capacity of the full battery assembled with the TiO2 pole piece without TBAF added was 145.183 mAh / g (calculated based on the mass of the negative electrode) at a rate of 0.5C, and the capacity retention rate after 100 cycles was 35%. Comparing the coulombic efficiency of the two batteries, the coulombic efficiency of the full battery assembled with the TiO2 pole piece with TBAF added can reach 98.9%, while the coulombic efficiency of the full battery assembled with the TiO2 pole piece without TBAF added is 95.9%. The full battery assembled with the TiO2 pole piece added with TBAF has a first-week discharge capacity of 100.136 mAh / g (calculated based on the mass of the negative electrode) at a rate of 10C, and a capacity retention rate of 83% after 2000 cycles. The results are recorded in Table 1.

[0100] The full battery assembled with the TiO2 pole piece added with TBAF was enlarged into a mAh-level soft-pack battery, the capacity of the soft-pack battery was 15.156 mAh, and the capacity retention rate was 71% after 1800 cycles at a rate of 0.5C. The results are recorded in Table 2.

[0101] The full battery assembled with TiO2 pole pieces added with TBAF was enlarged into an Ah-level soft-pack battery with a capacity of 1.236Ah and an energy density of 55Wh / kg. The capacity retention rate was 79% after 400 cycles at a rate of 1.5C. The energy efficiency of the battery was 90% at 1.5C. The results are recorded in Table 3.

[0102] Example 5

[0103] This embodiment provides a film-forming additive for an aqueous lithium-ion battery, which is CsF. In the aqueous lithium-ion battery, the negative electrode active material is anatase phase TiO2, the positive electrode active material is spinel phase LiMn2O4, the aqueous electrolyte is 13.8 mol / kg LiTFSI, and the solvent is water.

[0104] In this embodiment, the CsF film-forming additive is used as follows: 500 mg Li Mn2O4 and 25 mg CsF are added to an anhydrous ethanol solution, stirred at room temperature for 4 hours, and then dried at 100°C for 12 hours to obtain the final product Li Mn2O4-5 wt% CsF.

[0105] The full battery was assembled by using Li Mn2O4 with CsF added and Li Mn2O4 without CsF added as the positive electrode material, anatase phase TiO2 as the negative electrode material, 13.8 mol / Kg Li TFS I as the electrolyte, and aluminum foil as the current collector of the positive and negative electrodes. The full battery with Li Mn2O4 with CsF added had a discharge capacity of 104.695 mAh / g (based on the mass of the positive electrode) in the first week at a rate of 0.5C, and a capacity retention rate of 75% after 600 cycles. The full battery with Li Mn2O4 without CsF added had a discharge capacity of 103.825 mAh / g (based on the mass of the positive electrode) in the first week at a rate of 0.5C, and a capacity retention rate of 41% after 100 cycles. Comparing the coulombic efficiency of the two batteries, the coulombic efficiency of the full battery of Li Mn2O4 with CsF added can reach 98.8%, while the coulombic efficiency of the full battery of Li Mn2O4 without CsF added is 95.6%. The full battery of Li Mn2O4 with CsF added has a discharge capacity of 60.234 mAh / g (calculated based on the mass of the positive electrode) in the first week at a rate of 10C, and a capacity retention rate of 78% after 2000 cycles. The results are recorded in Table 1.

[0106] The LiMn2O4 full battery with added CsF was enlarged into a mAh-level soft-pack battery, the capacity of the soft-pack battery was 16.796mAh, and the capacity retention rate was 65% after 1900 cycles at a rate of 0.5C. The results are recorded in Table 2.

[0107] The LiMn2O4 full battery with CsF added was enlarged into an Ah-level soft pack battery. The capacity of the soft pack battery was 1.369Ah and the energy density was 54Wh / kg. The capacity retention rate was 77% after 600 cycles at a rate of 1.5C. The energy efficiency of the battery was 90% at 1.5C. The results are recorded in Table 3.

[0108] Example 6

[0109] This embodiment provides a film-forming additive for an aqueous lithium-ion battery, which is CsF. In the aqueous lithium-ion battery, the negative electrode active material is anatase phase TiO2, the positive electrode active material is spinel phase LiMn2O4, the aqueous electrolyte is 13.8 mol / kg LiTFSI, and the solvent is water.

[0110] In this embodiment, the CsF film-forming additive is used as follows: spinel phase LiMn2O4, conductive additive, CsF film-forming additive, and binder are prepared into electrode slurry in a mass ratio of 7:1.5:0.5:1, and the slurry is then coated on an aluminum foil current collector to form a positive electrode sheet.

[0111] The Li Mn2O4 pole piece with CsF added and the Li Mn2O4 pole piece without CsF added were used as the positive electrode material, anatase phase TiO2 was used as the negative electrode material, 13.8 mol / Kg Li TFS I was used as the electrolyte, and aluminum foil was used as the current collector of the positive and negative electrodes to assemble the full battery. The full battery assembled with the Li Mn2O4 pole piece with CsF added had a discharge capacity of 108.736 mAh / g (based on the mass of the positive electrode) in the first week at a rate of 0.5C, and a capacity retention rate of 83% after 550 cycles. The full battery assembled with the Li Mn2O4 pole piece without CsF added had a discharge capacity of 103.686 mAh / g (based on the mass of the positive electrode) in the first week at a rate of 0.5C, and a capacity retention rate of 43% after 100 cycles. Comparing the coulombic efficiency of the two batteries, the coulombic efficiency of the full battery assembled with the Li Mn2O4 pole piece with CsF added can reach 99.5%, while the coulombic efficiency of the full battery assembled with the Li Mn2O4 pole piece without CsF added is 96.8%. The full battery assembled with the Li Mn2O4 pole piece with CsF added has a discharge capacity of 68.937 mAh / g (calculated based on the mass of the positive electrode) in the first week at a rate of 10C, and a capacity retention rate of 85% after 2000 cycles. The results are recorded in Table 1.

[0112] The full battery assembled with LiMn2O4 pole pieces added with CsF was enlarged into a mAh-level soft-pack battery, the capacity of which was 16.143 mAh, and the capacity retention rate was 63% after 1750 cycles at a rate of 0.5C. The results are recorded in Table 2.

[0113] The full battery assembled with LiMn2O4 pole pieces added with CsF was enlarged into an Ah-level soft-pack battery. The capacity of the soft-pack battery was 1.596Ah and the energy density was 53Wh / kg. The capacity retention rate was 76% after 350 cycles at a rate of 1.5C. The energy efficiency of the battery was 88% at 1.5C. The results are recorded in Table 3.

[0114] Example 7

[0115] This embodiment provides a film-forming additive for aqueous lithium-ion batteries, which is tetrabutylammonium fluoride (C 16 H 36 NF, TBAF). In the aqueous lithium-ion battery, the negative electrode active material is anatase phase TiO2, the positive electrode active material is spinel phase LiMn2O4, the aqueous electrolyte is 13.8 mol / kg LiTFSI, and the solvent is water.

[0116] In this embodiment, the TBAF film-forming additive is used as follows: 500 mg LiMn2O4 and 25 mg TBAF are added to an anhydrous ethanol solution, stirred at room temperature for 4 hours, and then dried at 100°C for 12 hours to obtain the final product LiMn2O4-5 wt% TBAF.

[0117] The full battery was assembled with two materials, Li Mn2O4 with TBAF added and Li Mn2O4 without TBAF, as the positive electrode material, anatase phase TiO2 as the negative electrode material, 13.8 mol / Kg Li TFS I as the electrolyte, and aluminum foil as the current collector of the positive and negative electrodes. The full battery with Li Mn2O4 with TBAF added had a discharge capacity of 107.326 mAh / g (based on the mass of the positive electrode) in the first week at a rate of 0.5C, and a capacity retention rate of 87% after 450 cycles. The full battery with Ti O2 without TBAF added had a discharge capacity of 105.387 mAh / g (based on the mass of the positive electrode) in the first week at a rate of 0.5C, and a capacity retention rate of 35% after 100 cycles. Comparing the coulombic efficiency of the two batteries, the coulombic efficiency of the full battery of Li Mn2O4 with TBAF added can reach 99.6%, while the coulombic efficiency of the full battery of Li Mn2O4 without TBAF added is 95.3%. The full battery of Ti O2 with TBAF added has a discharge capacity of 67.235 mAh / g (calculated based on the mass of the positive electrode) in the first week at a rate of 10C, and a capacity retention rate of 82% after 2000 cycles. The results are recorded in Table 1.

[0118] The LiMn2O4 full cell with TBAF added was enlarged into a mAh-level soft-pack battery, the capacity of the soft-pack battery was 16.986 mAh, and the capacity retention rate was 67% after 1850 cycles at a rate of 0.5C. The results are recorded in Table 2.

[0119] The LiMn2O4 full cell with TBAF added was scaled up to an Ah-level soft-pack battery with a capacity of 1.236Ah and an energy density of 54Wh / kg. The capacity retention rate was 73% after 550 cycles at a rate of 1.5C. The energy efficiency of the battery was 90% at 1.5C. The results are recorded in Table 3.

[0120] Example 8

[0121] This embodiment provides a film-forming additive for aqueous lithium-ion batteries, which is tetrabutylammonium fluoride (C 16 H 36 NF, TBAF). In the aqueous lithium-ion battery, the negative electrode active material is anatase phase TiO2, the positive electrode active material is spinel phase LiMn2O4, the aqueous electrolyte is 13.8 mol / kg LiTFSI, and the solvent is water.

[0122] In this embodiment, the TBAF film-forming additive is used as follows: spinel phase LiMn2O4, conductive additive, TBAF film-forming additive, and binder are prepared into electrode slurry in a mass ratio of 7:1.5:0.5:1, and then the slurry is coated on an aluminum foil current collector to form a positive electrode sheet.

[0123] The Li Mn2O4 pole piece with TBAF added and the Li Mn2O4 pole piece without TBAF added were used as positive electrode materials, anatase phase titanium dioxide was used as negative electrode material, 13.8 mol / Kg Li TFS I was used as electrolyte, and aluminum foil was used as current collectors for positive and negative electrodes to assemble a full battery. The full battery assembled with the Li Mn2O4 pole piece with TBAF added had a discharge capacity of 105.364 mAh / g (based on the mass of the positive electrode) in the first week at a rate of 0.5C, and a capacity retention rate of 81% after 550 cycles. The full battery assembled with the Li Mn2O4 pole piece without TBAF added had a discharge capacity of 103.262 mAh / g (based on the mass of the positive electrode) in the first week at a rate of 0.5C, and a capacity retention rate of 37% after 100 cycles. Comparing the coulombic efficiency of the two batteries, the coulombic efficiency of the full battery assembled with the Li Mn2O4 pole piece with TBAF added can reach 99.6%, while the coulombic efficiency of the full battery assembled with the Li Mn2O4 pole piece without TBAF added is 95.9%. The full battery assembled with the Ti O2 pole piece with TBAF added has a discharge capacity of 65.696 mAh / g (calculated based on the mass of the positive electrode) in the first week at a rate of 10C, and a capacity retention rate of 85% after 2000 cycles. The results are recorded in Table 1.

[0124] The full battery assembled with the LiMn2O4 electrode added with TBAF was enlarged into a mAh-level soft-pack battery, the capacity of which was 15.763mAh, and the capacity retention rate was 76% after 1850 cycles at a rate of 0.5C. The results are recorded in Table 2.

[0125] The full battery assembled with LiMn2O4 pole pieces added with TBAF was enlarged into an Ah-level soft-pack battery with a capacity of 1.395Ah and an energy density of 52Wh / kg. The capacity retention rate was 83% after 450 cycles at a rate of 1.5C. The energy efficiency of the battery was 92% at 1.5C. The results are recorded in Table 3.

[0126]

[0127]

[0128] Table 1

[0129]

[0130] Table 2

[0131]

[0132] Table 3

[0133] By comparing the various performances of the aqueous battery film-forming additive used in the above examples with that of the aqueous battery film-forming additive not used, it can be seen that the aqueous battery film-forming additive provided by the present invention has outstanding technical advantages when applied to aqueous batteries, can effectively improve the energy density of aqueous lithium-ion batteries, and significantly improve the cycle performance of aqueous batteries. At the same time, it also has the advantages of convenient application and low cost.

[0134] The specific implementation methods described above further illustrate the objectives, technical solutions and beneficial effects of the present invention in detail. It should be understood that the above description is only a specific implementation method of the present invention and is not intended to limit the scope of protection of the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the scope of protection of the present invention.

Claims

1. An aqueous battery film-forming additive, characterized in that: The aqueous battery film-forming additive includes: fluoride AF soluble in aqueous solution, organic solution or ionic liquid; In the fluoride AF, F is a fluoride ion F - , A is a non-hydrated metal cation, including K + , Rb + , Cs + 、Tl + Sn 2+ 、Ag + , Sb 3+ One or more metal cations, and an amino group, when A is an amino group, the fluoride AF is a quaternary ammonium fluoride salt. The aqueous battery film-forming additive is used in the electrode of the aqueous battery; the electrolyte of the aqueous battery includes: a stable solution formed by dissolving a metal salt MX in an aqueous solution; in the aqueous battery, the fluoride AF undergoes a replacement reaction with the cations in the metal salt MX to generate a sparingly soluble fluoride MF on the negative electrode surface of the aqueous battery x solid electrolyte layer; wherein, X>0.

2. The aqueous battery film-forming additive according to claim 1, characterized in that: In the metal salt MX, M is a cation, including alkaline metal ions, alkaline earth metal ions, Zn 2+ or Al 3+ One or more of; X is an anion, including, CF3SO3 - TFSI - , FS I - BETI - ,OTf - 、BF4 - PF6 - 、AsF6 - 、CF3C00 - One or more of the .

3. The aqueous battery film-forming additive according to claim 1, characterized in that: The concentration of the electrolyte is 0.001 mol / kg-100 mol / kg; or, the concentration of the electrolyte is 0.001 mol / L-100 mol / L.

4. The aqueous battery film-forming additive according to claim 1, characterized in that: The solubility of the fluoride AF in aqueous solution, organic solution or ionic liquid is: within the temperature range of 0°C-100°C, the mass of the fluoride AF dissolved in every 100g of solvent is 0.01-1000g.

5. The aqueous battery film-forming additive according to claim 1, characterized in that: The non-hydrated metal cation A in the aqueous battery film-forming additive is used to modulate the double-layer structure of the negative electrode interface, thereby reducing the decomposition side reaction of the solvent molecules in the electrolyte at the negative electrode interface.

6. The aqueous battery film-forming additive according to claim 1, characterized in that: The non-hydrated metal cation A in the aqueous battery film-forming additive is used to induce the anions in the electrolyte to enter the double electric layer structure of the negative electrode interface under the interaction between anions and cations; Wherein, when the anion is CF3SO3 - TFSI - 、FSI - BETI - ,OTf - 、BF4 - PF6 - 、AsF6 - 、CF3C00 - When one or more of the above are present, during the cycle of the aqueous battery, when the potential of the negative electrode reaches a certain threshold, the F-containing group in the anion can continue to accept electrons to generate F - ; Thus, through the induction and electrochemical action of the non-hydrated metal cation A, the insoluble fluoride MF is further generated on the surface of the negative electrode x Solid electrolyte layer.

7. A method for applying an aqueous battery film-forming additive, characterized in that: The method comprises: adding the aqueous battery film-forming additive according to any one of claims 1 to 7 to an electrode active material dissolved in an aqueous solution, an organic solution or an ionic liquid, stirring, and then volatilizing the solvent to obtain an electrode material added with the aqueous battery film-forming additive; Among them, the mass of the aqueous battery film-forming additive accounts for 0.0001%-50.0000% of the total mass of the electrode material added with the aqueous battery film-forming additive; the stirring time is 1-100h; and the volatilization temperature is -100℃-1000℃.

8. An application method of an aqueous battery film-forming additive, characterized in that: The method comprises: mixing an electrode active material, the aqueous battery film-forming additive according to any one of claims 1 to 7, a conductive agent and a binder to prepare an electrode slurry, and coating the mixture on a current collector to obtain an electrode sheet; The mass of the aqueous battery film-forming additive accounts for 0.0001%-50.0000% of the total mass of the electrode material.

9. An electrode for an aqueous battery, characterized in that: The electrode comprises the aqueous battery film-forming additive described in any one of claims 1 to 7.

10. An aqueous battery, characterized in that: The aqueous battery comprises the aqueous battery electrode according to claim 9.

11. The aqueous battery according to claim 11, characterized in that: The positive electrode active materials of the aqueous battery include: Li Mn2O4, Li FePO4, Li CoO2, LiNi x Co y Mn 1-x-y O2、Li Ni x Co y Al 1-x-y Any of O2; wherein x>0, y>0, x+y<1; The negative electrode active material of the aqueous battery includes anatase TiO2, Ti O2 (B), Mo6S8, Li4Ti5O 12 , LiTi2(P04)3, graphite, or silicon.

12. The aqueous battery according to claim 11, characterized in that: The aqueous battery specifically includes: any one of an aqueous lithium battery, an aqueous sodium battery, an aqueous potassium battery, an aqueous zinc battery, an aqueous magnesium battery, an aqueous calcium battery, and an aqueous aluminum battery.

13. The aqueous battery according to claim 11, characterized in that: The aqueous battery is applied to energy storage power stations, mobile power sources for portable devices, and power devices for electric vehicles or hybrid electric vehicles.